Calcineurin inhibitor sparing regimens using m-target of rapamycin inhibitors: an opportunity to improve cardiovascular risk following kidney transplantation? - Zeier, Martin; Giet, Markus van der (Transplant international, 2011)
Maintenance therapy with calcineurin inhibitors (CNIs) increases cardiovascular risk. Use of the m-TOR inhibitors everolimus or sirolimus to minimize CNI exposure is usually undertaken to preserve renal function following kidney transplantation, but may also improve cardiovascular risk status. Recent studies of early conversion from CNI to m-TOR inhibitors have shown a numerical improvement in the incidence of hypertension, but results are not clear-cut. Dyslipidaemia, in contrast, is more frequent under m-TORs than with CNI-based immunosuppression. New-onset diabetes is rare (≤5%) using modern m-TOR regimens, for example, everolimus and reduced-exposure CNI. Renal function improvement with m-TOR inhibitor regimens versus CNIs would also be expected to improve cardiovascular risk. Moreover, m-TOR-based CNI-minimization regimens are not associated with proteinuria, a known cardiovascular risk factor, with the possible exception of late conversion in patients with poor renal function. Interestingly, m-TOR inhibitors may also exert cardioprotective effects. Animal data suggest that m-TORs may restrict the pathogenesis of atherosclerosis, consistent with preliminary clinical data that conversion from CNIs to everolimus can stabilize markers for arterial stiffness. In conclusion, use of m-TORs has the potential to lessen the toll of cardiovascular disease following kidney transplantation - an opportunity that merits further exploration.